NOVICE INVESTORS AND PROTECTION FROM SHORT SELLING CARRIED OUT BY SECURITIES BROKERS - Omardani, Guslan; Lestari, Rika (LPPM, Universitas Muhammadiyah Riau, 2024)
Domestic investors in the capital market until the end of July 2023 reached 11.4 million, and the increase in investors is seen as a positive development. However, on the other hand, Verdi Ikhwan, Head of the Research Division at the Indonesia Stock Exchange (IDX), stated that the level of capital market literacy has decreased from 4.92% to 4.11%. Meanwhile, inclusion has increased from 1.55% to 5.19%. It was also found that the Indonesia Stock Exchange (IDX) imposed sanctions on two securities for conducting short selling transactions without the exchange's approval. These two securities are PT Reliance Sekuritas Indonesia Tbk. (RELI) and PT Valbury Sekuritas Indonesia. The literacy level significantly influences the choices of novice investors in their activities in the capital market, particularly those who use brokers in stock trading. In this research, two problem formulations are posed: